Cognitive Impairment and Structural Neuroimaging Abnormalities Among Patients with Chronic Kidney Disease - Hai-Chen Pi; Yu-Feng Xu; Rong Xu; Zhi-Kai Yang; Zhen Qu; Yu-Qing Chen; Gui-Ling Liu; Jie Dong (Karger Publishers, 2016)
Background/Aims: Cognitive impairment and abnormal structural neuroimaging is common in chronic kidney disease patients. We aimed to explore its association with dialysis modality and the relationship between cognitive impairment and abnormal structural neuroimaging. Methods: Sixty peritoneal dialysis patients and 30 hemodialysis and 30 non-dialyzed stage 3-5 chronic kidney disease patients without history of stroke were enrolled for the study. Participants were matched for age, gender, education, diabetes status, and dialysis duration (if appropriate). Cognitive functions were measured using a battery of recognized instruments. Brain features were examined with 3-dimensional magnetic resonance imaging. Results: Cognitive impairment was significantly more severe in dialysis patients than in non-dialyzed patients. The global and specific cognitive function were not significantly different between patients on peritoneal dialysis and hemodialysis. Hemodialysis patients had more severe white matter hyperintensity, sulcal and ventricular atrophy, and SVIs than other patients. In all groups, higher white matter grade, ventricular grade, and hippocampal atrophy were significantly associated with global cognitive impairment, with hazard ratios of 1.80 (1.22-2.64), 1.67 (1.09-2.57), and 2.49 (1.07-5.77), respectively. White matter grade was also significantly associated with delayed memory (hazard ratio 1.63; 1.12-2.39). Conclusion: Dialysis modality showed no association with cognitive impairment, although hemodialysis patients had more severe neuroimaging abnormalities. For the whole group, white matter hyperintensity, and ventricular and hippocampal atrophy, were independently associated with global cognitive impairment in chronic kidney disease patients.